25th Anniversary Article: Semiconductor Nanowires – Synthesis, Characterization, and Applications. (6th March 2014) - Dasgupta, Neil P.; Sun, Jianwei; Liu, Chong; Brittman, Sarah; Andrews, Sean C.; Lim, Jongwoo; Gao, Hanwei; Yan, Ruoxue; Yang, Peidong
<x xml:space="preserve">Abstract</x> Semiconductor nanowires (NWs) have been studied extensively for over two decades for their novel electronic, photonic, thermal, electrochemical and mechanical properties. This comprehensive review article summarizes major advances in the synthesis, characterization, and application of these materials in the past decade. Developments in the understanding of the fundamental principles of "bottom‐up" growth mechanisms are presented, with an emphasis on rational control of the morphology, stoichiometry, and crystal structure of the materials. This is followed by a discussion of the application of nanowires in i) electronic, ii) sensor, iii) photonic, iv) thermoelectric, v) photovoltaic, vi) photoelectrochemical, vii) battery, viii) mechanical, and ix) biological applications. Throughout the discussion, a detailed explanation of the unique properties associated with the one‐dimensional nanowire geometry will be presented, and the benefits of these properties for the various applications will be highlighted. The review concludes with a brief perspective on future research directions, and remaining barriers which must be overcome for the successful commercial application of these technologies.